2010
DOI: 10.1029/2010gc003130
|View full text |Cite
|
Sign up to set email alerts
|

An analytical benchmark with combined pressure and shear loading for elastoplastic numerical models

Abstract: [1] We discuss the benchmark strategy to check the accuracy of elastoplastic numerical solutions based on a fully two-dimensional analytical solution. Associated rate-independent non-hardening plasticity with von Mises or Tresca criteria is assumed throughout. Algorithms for integration of the rate equations, strategies for stress updating over a time step, and tangent operators are discussed. The accuracy of a simple incremental algorithm as a function of the time step is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…Localizing plastic deformation is well known to be complicated to model numerically (e.g. Yarushina et al, 2010). Thus, I make a call to the community in order to improve this benchmark with high resolution models, similar perhaps to those that have been conducted for the problem of fault propagation in accretionary prisms (Buiter at al., 2008).…”
Section: Numerical Modeling Of Inflating Magma Chambers Numerical Metmentioning
confidence: 99%
See 1 more Smart Citation
“…Localizing plastic deformation is well known to be complicated to model numerically (e.g. Yarushina et al, 2010). Thus, I make a call to the community in order to improve this benchmark with high resolution models, similar perhaps to those that have been conducted for the problem of fault propagation in accretionary prisms (Buiter at al., 2008).…”
Section: Numerical Modeling Of Inflating Magma Chambers Numerical Metmentioning
confidence: 99%
“…A collective project such as that developed to compare the geometry of faults in thrust nappes (Buiter et al, 2008) would be recommended. This latter benchmark showed that whereas results are qualitatively similar, it remains difficult to match shear band geometries exactly, since the highly non-linear process of failure depends on specific formulations used in each numerical method (e.g .Kaus, 2010; Yarushina et al, 2010).…”
Section: A3) Benchmarks Without Gravity ∆P= 15 and 18 Mpamentioning
confidence: 99%
“…This assumption requires that the inner cavity is fully enclosed by a continued plastic region. Limit conditions of this requirement will be approached while the vertices of the predicted elastic‐plastic boundary in the minor axis direction just reach the cavity wall . It gives bep=α()1||βR. Intermediate principal stress …”
Section: Discussion On Restrictions From the Assumptionsmentioning
confidence: 99%
“…As an extension of Galin's solution, this solution aims to provide an analytical method for the static stress analysis of the soil around a cavity under conditions of the following: ( a ) The inner cavity is fully enclosed by a connected plastic region, and the plastic stress field is statically determinate; ( b ) the plastic zone is developed under monotonic loading, and no elastic unloading occurs in any case; and ( c ) the out‐of‐plane stress component σ zz always remains as the intermediate principal stress regardless of other stresses …”
Section: Static Stress Analysismentioning
confidence: 99%
See 1 more Smart Citation